The religious transformation of Gen Z in the new media era - Pabbajah, Mustaqim (Islamic Communication Journal, 2024)
New Media becomes an effective bridge of religious transformation in Gen Z. The presence of new media with various features offered is a new way of obtaining religious knowledge.  This paper wants to explain that there has been a diverse religious pattern of Gen Z experiencing transformation due to the intensity of the use of religion-based new media. The research in this study was conducted through observations, interviews and literature studies related to the formal objects, material objects and contexts studied, then analyzed with a qualitative descriptive approach. The results of this study explain the forms of religious transformation of Gen Z in the midst of the rise of new media. The transformation occurs due to the emergence of new media that offers various religion-based platforms. The implication is that intense religious learning accessed through new media can be said to be not in line with the ideally expected understanding of religion. In other words, religious understanding, which is actually the main orientation in religious learning, has undergone a transformation as shown by the religious experience of Gen Z. Where the presence of new media can be a tool that can change a person's paradigm in religion. This study suggests the need for a balance between media literacy and religious literacy to be balanced, along with the intensity of technological penetration that is continuously evolving.*****Media Baru menjadi jembatan tranformasi agama yang efektif pada Gen Z. kehadiran media baru dengan berbagai fitur yang ditawarkan menjadi cara baru dalam mendapatkan pengetahuan agama.  Tulisan ini hendak menjelaskan bahwa telah terjadi pola beragama beragam Gen Z mengalami transformasi akibat intensitas penggunaan new media berbasis agama. Penelitian dalam ttudi ini dilakukan melalui observasi, wawancara dan studi litertur terkait objek formal, objek material dan konteks yang dikaji, kemudian dianalisis dengan pendekatan deskriptif kualitatif. Hasil studi ini menjelaskan terkait bentuk-bentuk transformasi beragama Gen Z di tengah maraknya media baru. Transformasi itu terjadi akibat munculnya media baru yang menawarkan berbagai platform yang berbasis agama. Implikasinya adalah pembelajaran agama yang intens diakses melalui media baru dapat dikatakan belum sejalan dengan pemahaman agama yang diharapkan secara ideal. Dengan kata lain, pemahaman agama yang sejatinya menjadi orientasi utama dalam pembelajaran agama telah mengalami transformasi sebagaimana pengalaman beragama yang diperlihatkan Gen Z. Di mana kehadiran media baru dapat menjadi alat yang dapat mengubah paradigma seseorang dalam beragama. Studi ini menyarankan perlunya keseimbangan antara literasi media dan lierasi agama dapat seimbang, seiring dengan intensitas penetrasi teknologi yang terus berkembang.